Oxidation state analysis of LiFeSixP1-xO4/C (x = 0.06) with X-ray absorption near edge structure (XANES) in Fe K-edge and Si K-edge - Sahara Hamas Intifadhah; Vera Laviara Maghfirohtuzzoimah; Pelangi Az-zahra; Wantana Klysubun; Fahmi Astuti; Mochamad Zainuri; Darminto Darminto (Journal of Physics: Theories and Applications, 2021)
The development of LiFePO4 as a cathode materials on lithium-ion battery was increased with the use of additional techniques such as atomic doping and coating. The material used in this report was LiFeSi0.06P0.94O4/C (LFP Si-6%), synthesized with doping silicon 6% and 11wt% carbon coating by a solid state method. X-ray Absorption Spectroscopy (XAS) characterization was used to investigate the effect on electronic and atomic structure of LFP Si-6%, especially in X-ray Absorption Near Edge Strucuture (XANES) region. XANES data measured on Fe K-edge and Si K-edge. Fe foil, FeO, Fe2O3, FePO4, Si powder, SiO, SiO2 were used as a standard sample for comparison with the result of LFP Si-6%. XANES analysis showed that the energy absorption of Fe K-edge and Si K-edge in LFP Si-6% was 7124.94 eV and 1846.16 eV, respectively. The oxidation state of Fe was Fe2.576+ between Fe2+ and Fe3+, while Si was close to the estimation of Si4+. In addition, the linear combination fitting (LCF) in XANES Fe K-edge was performed to show the ratio of Fe2+/Fe3+ (FeO/Fe2O3).